Measuring Health Literacy Among French Pupils With the Health Literacy Survey Child Questionnaire-15 (HLS-Child-Q15) - Marine Cécile Genton; Boris Chapoton; Sali Mohammed Dauda; Mathieu Oriol; Véronique Regnier Denois; Franck Chauvin (SLACK Incorporated, 2023)
Background: Health literacy is a critical health determinant. To implement initiatives aiming at improving health literacy among children, adapted measurement tools are needed. Objective: This study aimed to translate, adapt, and test the Health Literacy Survey Child Questionnaire-15 (HLS-Child-Q15) to assess health literacy among French-speaking 8- to 11-year-old pupils. Methods: The HLS-Child-Q15 was translated and adapted to the French context to become the HLS-Child-Q15-FR. A cross-sectional survey was carried out using a written, self-reported questionnaire to assess the psychometric properties of the HLS-Child-Q15-FR. Key Results: Translation and adaptation of the HLS-Child-Q15 German-French translated versions were cross-referenced. Back-translation led to minor refinements. Qualitative pre-test among children led to simplifications in wording and structure. Validation of the HLS-Child-Q15-FR. Four trained interviewers collected data among 3,107 pupils in 74 elementary schools of the Auvergne-Rhône-Alpes region. HLS-Child-Q15-FR showed good reliability (alpha = 0.83). Exploratory factor analysis showed a two-factor model related to health care and primary prevention. Construct validity analyses suggested removing 3 items. External validity analyses indicated a significant and moderate relationship with perceived self-efficacy. Conclusion: This study aimed to address the issue of measuring health literacy among French-speaking 8- to 11-year-old pupils. The HLS-Child-Q15-FR showed a high internal consistency. Statistics suggested a two-dimensional thematic scale. These findings should be further investigated. [HLRP: Health Literacy Research and Practice. 2023;7(3):e144-e153.]